The trends of students in the Department of physical and Sports Education toward joining the administration of sports associations - Bouaicha , Lakhdar (sports creativity, 2025)
The aim of this study was to learn the direction of students in the Department of physical and Sports Education at the University of Anaba toward the work of the group of sports, where we have raised the main problem that is involved in what are the trends of the students in the Department of physical Education toward working in the administration of sports associations? Do you have differences in the answers of the researchers, which are attributed to the change of sex and specialization? After statistical processing and data collection, the results came to give a perception of a neutral trend toward working in the management of sports associations, with no differences in the responses of the research recipients according to the changes in gender and specialization. The researcher recommends that new content be included that contributes to students' knowledge of the physical and legal aspects of the work of the athletic society, especially in addition to proposing amendments to the law on sports associations